THE EFFECT OF REWARDS AND PUNISHMENT ON WORK MOTIVATION OF PERMANENT EMPLOYEES IN A PALM OIL MILL - Yael Febrian Purba; Yose Andre Sinuhaji (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Rewards and punishments are important aspects of Human Resource management that directly influence employee work motivation. In the palm oil mill industry, where productivity and work efficiency significantly influence operational success, understanding the impact of rewards and punishments on employee work motivation is crucial. Motivation is a psychological drive that drives a person to take action to achieve a specific goal. Motivation involves desires, needs, or goals that drive a person's behavior, both consciously and unconsciously. This research was conducted at the PT. Subur Arum Makmur-2 palm oil mill from October 2025 to January 2026, with the aim to determine the effect of rewards and punishments on the work motivation of process employees in the palm oil mill. This research used a quantitative descriptive method, and the population and sample consisted of 43 process employees, both shift 1 and shift 2. Data processing used SPSS version 22 software and testing included validity and reliability tests, classical assumption tests, and multiple linear regression analysis. Based on simultaneous testing, the F-count value is 4.417 with a significance level of 0.018, while the F-table is 3.23. Thus, F-count > F-table, it can be concluded that rewards and punishments significantly influence the work motivation of PKS employees. PT. Subur Arum Makmur-2.